Экономические факторы политического успеха: анализ на примере последних президентских выборов в Украине - Каревина, Е. (Социология: теория, методы, маркетинг, 2001)
The article is devoted to the problem of electoral success as an aspect of political success. An approach to study of economical determinants of political success is proposed. The problem of consistent of the voter’s economical preferences and political subject’s position is analyzed. There are presented the results of the content-analysis of political platforms of the most successful in the first tour of president election candidates (L.Kuchma, P.Simo - nenko, N.Vitrenko) and the data of empirical research held after election.